Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Menerapkan Metode MOORA - Wanda Abdi Setiawan; Raffa Dafa Arianda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Employees are part of the company's core assets to maintain its ability to survive and compete. In this case, employees need to have skills, even skills, to improve jobs in the company. In order for employees to be better protectors, there must be a system in place to help select the best employees who need decision support. Decision support is a computer system that is used to solve problems, generate information used to make decisions. The MOORA method is a multi-purpose optimization method. If the MOORA method is compared to the MOORA method, negative performance scores in the MOORA method do not appear and the MOORA method is less sensitive to large variations in criterion values. Multi-objective optimization-based ratio analysis (MOORA) is one of the supporting methods for identifying the best option that satisfies the extraction matrix